2020
DOI: 10.1038/s41564-020-0743-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide associations of human gut microbiome variation and implications for causal inference analyses

Abstract: Recent population-based 1-4 and clinical studies 5 have identified a range of factors associated with human gut microbiome variation. Murine quantitative trait loci 6 , human twin studies 7 and microbiome genome-wide association studies (mGWAS) 1,3,8-12 have provided evidence for genetic contributions to microbiome composition. Despite this, there is still poor overlap in genetic association across human studies. Using appropriate taxon-specific models along with support from independent cohorts, we show assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
180
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(195 citation statements)
references
References 67 publications
10
180
0
5
Order By: Relevance
“…To expand these findings and further dissect the complex pathogen-colonization patterns in humans, we utilized host genome-wide associations with human gut microbiome variation for 155 pathogens (Hughes et al, 2020) identified through 16S rRNA sequencing. For example, among the top SNP associations with Desulfovibrionaceae (p<0.0001), a sulfatereduced bacterium associated with intraabdominal infections and inflammatory bowel disease (Goldstein et al, 2003;Loubinoux et al, 2002), we observed an enrichment for SNPs associated with intestinal infection in BioVU ( Figure 5C).…”
Section: Serology and Culture Data Reveal Insights Into Clinical Infementioning
confidence: 99%
See 3 more Smart Citations
“…To expand these findings and further dissect the complex pathogen-colonization patterns in humans, we utilized host genome-wide associations with human gut microbiome variation for 155 pathogens (Hughes et al, 2020) identified through 16S rRNA sequencing. For example, among the top SNP associations with Desulfovibrionaceae (p<0.0001), a sulfatereduced bacterium associated with intraabdominal infections and inflammatory bowel disease (Goldstein et al, 2003;Loubinoux et al, 2002), we observed an enrichment for SNPs associated with intestinal infection in BioVU ( Figure 5C).…”
Section: Serology and Culture Data Reveal Insights Into Clinical Infementioning
confidence: 99%
“…PrediXcan genetic associations for 35 ID traits This paper phewascatalog.org PrediXcan (Gamazon et al, 2018;Gamazon et al, 2015) https://github.com/hakyimlab/Predi Xcan MultiXcan (Barbeira et al, 2019) https://github.com/hakyimlab/multix can-paper GTEx (2015;Battle et al, 2017;Consortium, 2013) https://gtexportal.org/home/ Gene Set Enrichment Analysis (GSEA) (Subramanian et al, 2005) http://software.broadinstitute.org/g sea/index.jsp Human gut microbiome GWAS (Hughes et al, 2020) https://data.bris.ac.uk/data/dataset/ f12b2cf665593ac466149cc6da3ca 867…”
Section: Key Resources Tablementioning
confidence: 99%
See 2 more Smart Citations
“…The authors estimate that non-genetic and genetic factors account each for 10% of gut microbiota variations. A recent study conducted in a large cohort of Flemish and German individuals lead to the identification of further genetic associations involving multiple microbial traits, including that between a single nucleotide polymorphism (SNP) on the RAPGEF1 gene, which is involved in the regulation of the gastrointestinal tract’s physiology, and Ruminococcus [ 11 ].…”
Section: Introductionmentioning
confidence: 99%